2013
DOI: 10.1186/1746-4811-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for variation in designing greenhouse experiments with special reference to greenhouses containing plants on conveyor systems

Abstract: BackgroundThere are a number of unresolved issues in the design of experiments in greenhouses. They include whether statistical designs should be used and, if so, which designs should be used. Also, are there thigmomorphogenic or other effects arising from the movement of plants on conveyor belts within a greenhouse? A two-phase, single-line wheat experiment involving four tactics was conducted in a conventional greenhouse and a fully-automated phenotyping greenhouse (Smarthouse) to investigate these issues.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 19 publications
(32 reference statements)
2
49
0
Order By: Relevance
“…Such environmental homogeneity may also be achieved by efficient use of experimental design and analysis within the HTPP framework (e.g., choosing suitable block size and/or using appropriate statistical models for the analysis) with less cost than relocating the plants [14]. However, it has been reported that the QTLs identified in controlled environments may not contribute to crop improvement in the field [6].…”
Section: Trendsmentioning
confidence: 98%
“…Such environmental homogeneity may also be achieved by efficient use of experimental design and analysis within the HTPP framework (e.g., choosing suitable block size and/or using appropriate statistical models for the analysis) with less cost than relocating the plants [14]. However, it has been reported that the QTLs identified in controlled environments may not contribute to crop improvement in the field [6].…”
Section: Trendsmentioning
confidence: 98%
“…They also stated that temperature variations inside greenhouses may affect processes such as plant growth and the distribution of pests. Using large climate-controlled greenhouses equipped with computercontrolled conveyor belts carrying up to 600 plants per room, Brien et al (2013) concluded that accounting for the variation in microclimate in a greenhouse is improved using statistical design and analysis rather than rearranging the position of plants during the experiment. However, in many cases, due to financial constraints, greenhouses are not climate-controlled or are only partly so, resulting in microclimate spatial heterogeneity.…”
mentioning
confidence: 99%
“…Microclimate effects are common in glasshouse environments and these effects are generally predictable over extended periods of time [18,19]. As such, systematic blocking designs will generally be more effective in accounting for microclimate variation than rearrangement approaches [15].…”
Section: Guidelines For Glasshouse and Growth Chamber Researchmentioning
confidence: 99%
“…We strongly discourage option (b) for four reasons: (1) rearrangement of experimental units increases the workload and creates more opportunities for mistakes in randomization or damage to plants [17]; (2) successful application of this approach requires that experimental units spend similar amounts of time within each microclimate [15]; (3) there is no evidence that this approach will lead to greater precision than the use of formally randomized designs, because the rearrangement either eliminates or creates significant challenges in accounting for spatial or microclimate variation; and (4) there are numerous alternative experimental design options ranging in both complexity and expected effectiveness. Microclimate effects are common in glasshouse environments and these effects are generally predictable over extended periods of time [18,19].…”
Section: Guidelines For Glasshouse and Growth Chamber Researchmentioning
confidence: 99%
See 1 more Smart Citation